Influence of the domestic COVID-19 pandemic on the pediatric emergency department - Chen, Ying-Ju; Chen, Chun-Yu; Lee, En-Pei; Huang, Wun-Yan; Wu, Han-Ping (Frontiers in Medicine, 2022)
Objectives After the coronavirus disease 2019 (COVID-19) pandemic emerged, there has been a substantial decline in emergency department (ED) visits. However, the impact of the pandemic on pediatric ED (PED) visits has not been well discussed. This study aimed to compare the epidemiology and clinical characteristics of PED visits before and after the time of the COVID-19 outbreak. Methods Data of pediatric patients admitted to the PED between February 2019 and January 2021 were retrospectively collected. All patients were divided into two groups: 1 year before the COVID-19 pandemic (group 1) and 1 year after the COVID-19 outbreak (group 2). Basic demographics, clinical characteristics, triage levels, categories of diagnosis at PED, disposition, and hospitalization rates (wards and intensive care units) were further analyzed and compared between the two groups. Results During the study period, 48,146 pediatric patients were enrolled (30,823 in group 1, and 17,323 in group 2). PED visits represented a 43.8% annual decline. The most common diseases in the PED in group 1 were infectious diseases, whereas digestive system diseases were the most common diseases in group 2 (both P < 0.001). In group 2, shorter PED observational time, longer hospital stay, and higher admission rates were noted compared to those in group 1 (all P < 0.001). Conclusion During the COVID-19 pandemic, the proportion of respiratory system diseases and infectious diseases sharply decreased in the PED, whereas the proportion of digestive system diseases relatively increased. The COVID-19 pandemic has impacted the nature of PED visits and we should pay more attention on digestive system diseases and the rates of out-of-hospital cardiac arrest and overall mortality.